Braf-Mutant Melanomas: Biology and Therapy - Elvira Pelosi; Germana Castelli; Ugo Testa (Current Oncology)
The incidence of melanoma, the most lethal form of skin cancer, has increased mainly due to ultraviolet exposure. The molecular characterization of melanomas has shown a high mutational burden led to the identification of some recurrent genetic alterations. BRAF gene is mutated in 40–50% of melanomas and its role in melanoma development is paramount. BRAF mutations confer constitutive activation of MAPK signalling. The large majority (about 90%) of BRAF mutations occur at amino acid 600; the majority are BRAFV600E mutations and less frequently BRAFv600K, V600D and V600M. The introduction of drugs that directly target BRAF-mutant protein (BRAF inhibitors) and of agents that stimulate immune response through targeting of immune check inhibitor consistently improved the survival of melanoma BRAFV600-mutant patients with unresectable/metastatic disease. In parallel, studies in melanoma stage II-III patients with resectable disease have shown that adjuvant therapy with ICIs and/or targeted therapy improves PFS and RFS, but not OS compared to placebo; however, neoadjuvant therapy plus adjuvant therapy improved therapeutic response compared to adjuvant therapy alone.